Effect of solvent polarity during electrodeposition of asphaltenes from a Colombian oil in the presence of a magnetic field and magnetic nanoparticles. (July 2020) - Roa, M; Amaya, I; Correa, R
Abstract: This work focuses on analyzing the electrokinetic behavior of asphaltenes of extra heavy oil. For this, electrodepositions were carried out in asphaltene solutions (4 %w/w) with two solvents of different polarities: toluene and chloroform. In addition, we worked with different magnetic fields, and the effect of adding 1% w/w of magnetic nanoparticles was analyzed. The asphaltenes were extracted with heptane and were characterized by infrared and ultraviolet visible spectroscopy. In the case of toluene, the initial adsorption (without fields) was 4 mg in both anode and cathode. By using an electric field (100 V/m) the deposits increased to 6 mg (anode) and 5 mg (cathode). However, when using a static magnetic field of 0.1 mT, no changes were observed. But, by modifying said field by a dynamic one (0.1 mT and 60 Hz), 15 mg (anode) and 19 mg (cathode) were obtained. Moreover, the addition of nanoparticles (previously characterized by scanning electron microscopy and X ray diffraction) changed the behavior, worsening in the absence of fields, and improving only in the presence of the dynamic field (104 mg, 26 mg in anode and cathode, respectively). Similar results were obtained when using chloroform. Thus, the best performance was obtained by using a dynamic magnetic field. By not considering the nanoparticles, total deposits increased more than 14 times (102 mg versus 7 mg). However, considering them, the increase was greater than 30 times (302 mg versus 10 mg). Therefore, we consider that adding nanoparticles, and supporting the electrodeposition process with a dynamic magnetic field, is an alternative that must be included to improve process performance.